WRITING STRATEGIES OF INDONESIAN UNDERGRADUATE EFL STUDENTS IN A MULTILINGUAL CONTEXT - Ida Zuraida Supri; Ervina CM Simatupang; Heri Heryono (University of Kuningan, 2026)
This study identifies and describes the writing strategies used by Indonesian undergraduate students in an English Department within a multilingual context. A quantitative survey was conducted with 76 students at a private university in Bandung, using a Likert-scale questionnaire to measure cognitive, metacognitive, affective, and social strategies. The results showed that students used a range of strategies, with cognitive strategies like brainstorming and rereading being most common, and metacognitive strategies, such as self-monitoring and feedback awareness, being more frequently employed. Affective strategies focused on emotional regulation and motivation, while social strategies highlighted peer collaboration and digital tools. The study provides insights into writing strategy use among Indonesian EFL students and suggests the need for explicit instruction in planning, research-based writing, and strategy development. Due to its limited scope, the findings are not intended to be broadly generalized.